Incidence of Anemia and Adherence to Fe Tablet Consumption Based on MCH Book Completion - Lenny Irmawaty Sirait; Tarmuni Tarmuni; Friska Junita; Tiago Silva; Costa Rita (Journal of World Future Medicine, Health and Nursing, 2023)
Maternal mortality is a measure of welfare and health status in a country. The death of 1320 mothers in Indonesia is caused by bleeding, one of which is caused by anemia during pregnancy. The success of supplementing 90 Fe tablets in Indonesia is 51% and only 37.7% of pregnant women consume 90 tablets of Fe tablets. Pregnant women and giving 90 iron tablets in West Java Province amounted to 98.2%, or 943.34 people and there was a jump of 0.5% or 5,505 pregnant women did not get Fe tablets. One way to monitor the consumption of FE tablets is through the MCH book. Research Objectives: To determine the relationship between consumption of Fe tablets in terms of filling out the MCH handbook and the incidence of anemia in third trimester pregnant women at the Cipayung Health Center in 2022. Research Methods: This study used the chi square method where observations were made of pregnant women at one time to measure the relationship between consumption adherence FE tablets with the incidence of anemia. The sample used in this study were 33 people who met the inclusion and exclusion criteria. Research Results: demo data obtained the average age of the mother is 31 years. Mother's education 54.5% have higher education. As many as 84.4% of mothers have high knowledge. As many as 66.7% of the 21 pregnant women who adhered to the consumption of FE tablets did not experience anemia. Statistical tests showed a P-value of 0.016 and there was a relationship between adherence to consumption of FE tablets and the incidence of anemia in third-trimester pregnant women at the Cipayung Health Center in 2022. Conclusion: monitoring of FE consumption can be done through the MCH handbook for pregnant women so that early prevention of anemia during pregnancy, especially when entering the third trimester.